Sentido antropológico-ético como responsabilidade pelo outro em E. Lévinas: uma análise dos códigos de ética profissional do psicólogo - Caixeta, Luís Vicente (2019)
This thesis reflects on the anthropological-ethical sense when it comes to Brazilian psychologists in the light of Emmanuel Lévinas' philosophical thinking regarding the phenomenon of ethical otherness, especially through the historical analysis of Psychologists’ Codes of Professional Ethics. That way, this theoretical qualitative research involved bibliographic research so as to examine the theme under a new perspective and obtain innovative conclusions. Professional ethics is guided by the Federal Council of Psychology based on the Codes of Ethics. The historicity of the Codes reveals the ethical foundation on the premise of respect for human dignity in light of the Universal Declaration of Human Rights (1948) and emphasizes the responsibility of psychologists, though through an abstract and normative discourse. Lévinas' philosophy is an alternative to the models of teleological and deontological ethics, because it aims at the meaning of otherness. The Other reveals itself as a vulnerable face in its enigmatic visit and claims for responsibility: an irreducible relationship of the human. By means of Levinasian ethical otherness, psychologists may find themselves free to respond to the Other and the whole community, regardless of reciprocity; also, professional’s subjectivity is constituted as fraternal intersubjectivity. Respect for human dignity has its meaning in otherness, not in knowledge and power over the other. Otherness immediately linked to the responsibility of psychologists as nurturing, as service, as love infinitely. Thus, anthropological-ethical sense of psychologists is revealed by ethics as responsibility for the other, which provides professional ethics of human psychologists through humanizing relationships.